AN ANALYSIS OF SOCIAL CONFLICT IN THE GRAND BUDAPEST HOTEL MOVIE BY WES ANDERSON - Ruqoyyah, Ruqoyyah; Muhajir, Fatimah; Prafitri, Wilma (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research is titled "An Analysis of Social Conflict in The Grand Budapest Hotel Movie by Wes Anderson" explores various types of social conflicts depicted in the movie. Released in 2014, The Grand Budapest Hotel is a comedy-drama that follows the adventures of Gustave H., a dedicated hotel concierge, and his assistant, Zero Moustafa, in a fictional Eastern European country. Using qualitative descriptive research methodology and drawing upon Lewis A. Coser's framework on social conflict and Deutsch theory on the causes of social conflict. The research aims to identify the types and causes of social conflict depicted in The Grand Budapest Hotel. This study identifies three main types of social conflict: Conflict of Social Position, Conflict of Interest, and Conflict of Role. The causes of these conflicts, as reflected in the movie, include differing expertise, rivalry for position, control, and recognition, personal dislike, diverse economic interests, and drive for autonomy.Keywords: Social Conflict, Conflict of Social Position, Conflict of Interest, Conflict of Role